PPP in OECD Countries: An Analysis of Real Exchange Rate Stationarity, Cross-Sectional Dependency and Structural Breaks (2012)
The stationarity of OECD real exchange rates over the period 1972-2008 is tested using a panel of 26 member countries. The methodology followed stems from the need to meet several key concerns: (i) the identification of which panel members are stationary; (ii) the presence of cross-sectional dependence among the countries in the panel; and (iii) the identification of potential structural breaks that might have occurred at different points in time. To address these concerns, we employ a recent test that examines the time series properties of the data within a panel framework, namely the Hadri and Rao (Oxford Bulletin of Economics and Statistics 70: 245-269, 2008) panel stationarity test. The real exchange rates of the 26 OECD countries are found to be stationary when considered as a panel, but only after allowing for endogenously-determined structural breaks and cross section dependence. We also find that once these structural breaks are removed from the underlying series, the half-life of shocks to the real exchange rate is much shorter than has been calculated in earlier studies. © 2011 Springer Science+Business Media, LLC.